Choir to Improve Congregational Musicality at Kemah Injil Indonesia Parousia Church (Jurnal Seni Musik, 2023)
The purpose of this study is to provide choir members with an understanding of the benefits of joining a congregational choir. The approach used in this study is a qualitative approach, data collection techniques using questionnaire techniques, interviews, observations. Based on the results of the research conducted, it shows that every congregation that involves itself in the choir gets new experiences and knowledge about music such as; Able to read notation well, and can sing correctly. Understand vocal techniques, master the voice divisions of soprano, alto, tenor, bass. In addition to gaining experience in terms of music, the Congregation also learns to socialize with others, such as mutual respect. In addition, the congregation can lead the choir, understand the dynamics in the song.